Development And Application Of Ceramic Media Disk Filter Technology At Phelps Dodge Morenci, Inc. (SME Convention February 1994 Albuquerque, New Mexico ) - Christopher B. Kapes (Society for Mining, Metallurgy & Exploration, 1994)
To reduce concentrate dewatering and drying costs, the Concentrator Division at Phelps Dodge Morenci, Inc. investigated available filtration technologies. Numerous methods were explored, including: drum, disk, belt, pressure, hyperbaric, and ceramic media filtration. An economic evaluation of the individual filtration technologies indicated the advantages of ceramic media filtration for Morenci concentrates. This paper discusses the technological development culminating in the first full scale application of ceramic media disk filters in North America. Low moisture contents are obtained at high production rates and greatly reduced operating costs.